Analysis Of Genetic Diversity In Parents And Hybrids Of Populus Deltoides Bartr. Using Microsatellite Markers (Applied Biological Research, 2018)
Molecular markers have proved a valuable source for assessing plant genetic  resources by improving our understanding on the distribution and extent of  genetic variability present within and among the species. In this study, genetic  diversity among and between 16 parents and 12 hybrids of Populus deltoides  were analyzed by SSRs (simple sequence repeats). The 18 selected SSR  primers yielded 51 polymorphic scorable bands with PIC value of 0.77. The  effective multiplex ratio and marker index were 1.82 and 0.80, respectively.  Genetic similarity among the collections varied from 0.39 to 0.88 when pooled  data of parents and hybrids were analyzed through UPGMA. The analysis of  combined data set with SSR, clustered hybrids on dendrogram based on their  relationship with parents. Thus, high polymorphism obtained indicates that  SSR markers have potential for identification and characterization of genetic  variation within and among Populus species.
Keywords: Genetic diversity; germplasm; hybrids; molecular markers; Populus deltoids; simple sequence repeat